Formulation and Development of Bar Soap from Moringa Leaf Extract (Moringa Oleifera) a Natural Solution for Skin Health - Arumsari, Alif Gita; Ardiansyah, Teguh; Ginting, Petrus Junake (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to develop bar soap by utilizing Moringa Oleifera leaf extract as the main active ingredient. Moringa leaves are known to be rich in antioxidants, vitamins, and minerals that are beneficial for skin health. Tests were conducted to evaluate the physical, chemical, and microbiological characteristics of the resulting bar soap. The results showed that bar soap from Moringa leaf extract has good cleaning properties, high antioxidant content, and positive effects on skin health, including hydration and free radical protection. Therefore, this bar soap has the potential to be an effective natural skin care product